2010
DOI: 10.1038/sc.2010.126
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a physical activity monitor for use on a wheelchair

Abstract: Study design: Keeping physically active is important for people who mobilize using a wheelchair. However, current tools to measure physical activity in the wheelchair are either not validated or limited in their application. The purpose of this study was to develop and validate a monitoring system to measure wheelchair movement. Methods: The system developed consisted of a tri-axial accelerometer placed on the wheel of a wheelchair and an analysis algorithm to interpret the acceleration signals. The two accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 17 publications
1
53
0
2
Order By: Relevance
“…4,8 A series of reports based on studies of activity evaluation devices in wheelchair-using persons after SCI has been published in recent years. [9][10][11][12][13][14][15] Coulter et al 9 and Sonenblum et al 10,11 conducted several studies using multiaxial or triaxial accelerometers mounted on the wheels of wheelchairs. However, if the work involves mainly tasks using active muscles in the upper limbs, conducting an evaluation of physical activity using devices reflecting the movements of the upper limbs would be both legitimate and rational.…”
Section: Introductionmentioning
confidence: 99%
“…4,8 A series of reports based on studies of activity evaluation devices in wheelchair-using persons after SCI has been published in recent years. [9][10][11][12][13][14][15] Coulter et al 9 and Sonenblum et al 10,11 conducted several studies using multiaxial or triaxial accelerometers mounted on the wheels of wheelchairs. However, if the work involves mainly tasks using active muscles in the upper limbs, conducting an evaluation of physical activity using devices reflecting the movements of the upper limbs would be both legitimate and rational.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that wheel rotation monitors can be used to assess mobility characteristics, activity levels, and wheelchair use of MWUs in laboratory, community and nursing home settings. [1][2][3][4] However, there are only a limited number of monitoring tools available for manual wheelchair users (MWUs). [2][3][4][5][6] This is especially striking as the general population can choose from a wide array of activity monitors to track their activities in the community in terms of steps, intensity of PA, duration of PA, and energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, there are only a limited number of monitoring tools available for manual wheelchair users (MWUs). [2][3][4][5][6] This is especially striking as the general population can choose from a wide array of activity monitors to track their activities in the community in terms of steps, intensity of PA, duration of PA, and energy expenditure. [7][8][9][10][11] The availability of activity monitors for MWUs can help researchers and clinicians in the fields of rehabilitation science, kinesiology, and health and physical activity to study mobility characteristics and evaluate mobility related interventions in this population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations